2011
DOI: 10.1021/es201842h
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Subfamily I.2.C Catechol 2,3-Dioxygenase mRNA Transcripts in Groundwater Samples of an Oxygen-Limited BTEX-Contaminated Site

Abstract: Low dissolved oxygen concentration of subsurface environments is a limiting factor for microbial aromatic hydrocarbon degradation, and to date, there are only a limited number of available reports on functional genes and microbes that take part in the degradation of aromatic hydrocarbons under hypoxic conditions. Recent discoveries shed light on the prevalence of subfamily I.2.C catechol 2,3-dioxygenases in petroleum hydrocarbon contaminated hypoxic groundwaters, and their considerable environmental importance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
46
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 46 publications
0
46
0
Order By: Relevance
“…The nod gene pools recovered from the two benzene, toluene, ethylbenzene, and xylene (BTEX)-impacted aquifers were strikingly different, possibly reflecting distinct contamination and redox scenarios at the sites (26)(27)(28). While the absolute abundance of the nod gene was one order of magnitude higher in Siklós than that in Flingern (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The nod gene pools recovered from the two benzene, toluene, ethylbenzene, and xylene (BTEX)-impacted aquifers were strikingly different, possibly reflecting distinct contamination and redox scenarios at the sites (26)(27)(28). While the absolute abundance of the nod gene was one order of magnitude higher in Siklós than that in Flingern (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The samples used in this study were collected from various sites, as listed in Table 2. Siklós sediment samples were collected in April 2015 from the bottom of monitoring well ST2 in the center of a xylene plume in Siklós, Hungary (26,27), while Flingern sediments were taken by push-coring from the upper fringe of a toluene plume (6.4 m below ground) in Flingern, Düsseldorf, Germany, in September 2013 (28,37). Sediments were transported to the lab in cooling boxes and were then frozen at Ϫ20°C before DNA extraction.…”
Section: Methodsmentioning
confidence: 99%
“…According to previous studies, Proteobacteria was found effective in removing the organic pollutants in water, thus playing a role in water purification (Táncsics et al, 2012). Also, the abundance of Proteobacteria was correlated with nutrient content in water.…”
Section: Discussionmentioning
confidence: 83%
“…In water, the content of Proteobacteria and COD in YK was found significantly higher ( p < 0.05) than that in the other regions, suggesting that there was certain correlation between the relative abundance of Proteobacteria and the content of organic matters in pond water. According to previous studies, Proteobacteria was found effective in removing the organic pollutants in water, thus playing a role in water purification (Táncsics et al, ). Also, the abundance of Proteobacteria was correlated with nutrient content in water.…”
Section: Discussionmentioning
confidence: 96%
“…Likewise, the catechol 2,3-dioxygenases encoded in the catabolic operons, together with this type of monooxygenase, have also been reported to perform efficiently under low-oxygen conditions (68). The appearance of genes encoding multicomponent monooxygenase and extradiol dioxygenases from the subfamily I.2.C type (18) has been detected in other hypoxic environments, indicating that these types of genes could have a relevant function in these type of systems, which has not been well studied or exploited yet (69,70).…”
Section: Discussionmentioning
confidence: 99%